The Importance of Price, Income, and Affordability in the Demand for Cigarettes in Spain - Cadahia, Pedro; Golpe, Antonio A.; Martín-Álvarez, Juan Manuel; Asensio, Eva (ADDICTA: The Turkish Journal on Addictions, 2023)
In the literature it is commonly accepted that the best mechanism to control smoking is by increasing tobacco prices via taxes. However, there are some studies that indicate that the decrease in tobacco consumption when prices rise is because consumer income is not capable of counteracting said rise. The empirical analysis was developed using a panel of data from the Spanish provinces covering 2002 to 2018. By using Machine Learning assembly models, the importance of price, GDP and affordability as a mechanism for controlling the demand for cigarettes is estimated. The importance of affordability to control tobacco consumption in Spain has grown over time. Furthermore, until 2010, income has generally better explained the demand for cigarettes in the Spanish provinces. However, as of 2010, price is the explanatory variable of the demand function that best explains the behavior of the demand for cigarettes. In these circumstances, the separate estimates of price and income elasticity that have been carried out in Spain so far must be interpreted considering that as of 2010, price is more important than income in explaining the demand for cigarettes. Furthermore, when the relative income price reaches 1%, there seems to be a positive relationship between this variable and the importance of price in explaining the demand for tobacco. Although the demand functions estimated so far are useful to make predictions about the behavior of cigarette demand, the government must consider that price is a good tool to control tobacco consumption from a certain point of affordability. Specifically, it appears that when the relative income price exceeds 1%, the importance of price as a tool to control legal cigarette sales grows each time the relative income price rises.
Keywords: economics; price; public policy; Emerging; Scopus